Professional Competence Study on Student of Informatics Engineering Education Study Program at Electrical Engineering Department - Wahyu Sakti Gunawan Irianto; Hakkun Elmunsyah; Muhammad Jauharul Fuady; Ananda Putri Syaviri (Pascasarjana Universitas Negeri Malang (UM), 2018)
Abstract: This research aims to reveal the basic programming competence of Informatics Engineering students using quantitative approach with ex post facto method. Population in this research is student of study program of Informatics Engineering of 2013, 2014, and 2015. Technique determination of popu-lation number and sample, researcher use stratified sampling and cluster sampling. Researchers use cluster sampling with the aim to choose which clusters will be taken to be more accurate in obtaining re-search data. The results of this study indicate that the students’ competence is very high with 0.757 and 0.748 of reliability value.Key Words: professional competence, ability in basic computer programming, test instruments, questionnaire instruments Abstrak: Penelitian ini bertujuan untuk mengungkap kompetensi pemrograman dasar mahasiswa Teknik Informatika menggunakan pendekatan kuantitatif dengan metode ex-post facto. Populasi dalam penelitian adalah mahasiswa program studi Teknik Informatika 2013, 2014, dan 2015. Teknik penentuan jumlah po-pulasi dan sampel, peneliti menggunakan stratified sampling dan cluster sampling. Peneliti menggunakan cluster sampling dengan tujuan untuk memilih lebih akurat kelompok mana yang akan diambil dalam memperoleh data penelitian. Hasil penelitian ini menunjukkan bahwa kompetensi mahasiswa sangat tinggi dengan nilai reliabilitas 0,757 dan 0,748.Kata kunci: kompetensi profesional, kemampuan pemrograman komputer dasar, instrumen tes, instrumen kuesioner